Calculation of the electron stopping power of some components of human body tissues - Itab F. Hussein; Rana O. Abdaljalil; Sahar A. Mohammed; Ahmed F. Mkhaiber (Kuwait Journal of Science)
The stopping power of the target material is an essential variable for evaluating the effects of radiation. In this study, the stopping power for an electron that interacts with some components of human body tissues (H, C, N, O, Na, P, S, Cl, K, Ca, Fe, I) was calculated using two methods: The Beth formula and the ESTAR code, in the energy range 0.01–1000 ​MeV. The total stopping power of these elements was calculated by adding their collisional stopping power to their radiative stopping power. The results from both methods were in good agreement. A semi-empirical formula was found to compute the total electron stopping power of electrons of these targets for a given electron energy. Our stopping power values show good agreement with ICRU 37 (1984).